ANALISIS PENERIMAAN TEKNOLOGI INFORMASI E-FILING PAJAK DENGAN MODEL INTEGRASI TECHNOLOGY ACCEPTANCE MODEL DAN THEORY OF PLANNED BEHAVIOR (Studi Pada Dosen dan Staf Administrasi Fakultas Ekonomi dan Bisnis Universitas Brawijaya) - WIDAYANTI, GITA SARASTYA (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The largest source of Indonesian income is tax. The development of information technology is one of the governments concerns, in which they use it in tax reporting system by providing e-Filing for annual tax return reporting. E-Filing is an electronic way of submitting annual tax return online and real time via the internet on the website of the Directorate General of Tax (www.pajak.go.id). This study aims to determineindividual perceptions that affect the intention of taxpayers to use e-Filing to report their annual tax returns. The independent variables of this study are perceived usefulness, perceived ease of use, perceived behavioral control, and subjective norms, and the dependent variable is the intention to use e-Filing. The respondents of this study are lecturers and administrative staff of Faculty of Economics and Business in BrawijayaUniversity. This study uses multiple linear regression analysis to examine the relationship between the independent and the dependent variables. The number of the sample is determined using Roscoe technique, where the number of the variable is multiplied by ten, resulting in 50 samples and becoming the number of the respondents from which the data were obtained and then processed. The results of the hypothesis testing showthat perceived usefulness and perceived behavioral control positively influence the intention to use e-Filing, but perceived ease of use and subjective norms do not affect it. Â Keywords: intention, E-filing, perceived usefulness, perceived ease of use, perceived behavioral control, subjective norms